Characterization of a more sustainable cement produced with recycled drywall and plasterboards as set retarders. (15th October 2016) - Flores Medina, Nelson; Hernández-Olivares, F.; Arroyo, Xabier; Aguilera, Amador; Fernandez, F.
Highlights: RCS can be used as set retarders in cement. Porosity of cements with RCS has been studied through image analysis. Cement samples with RCS treated at temperatures over 150 °C comply cement standards. The porosity of cement is reduced when RCS are preheated. The management of RCS facilitates the manufacture of more sustainable cements. Abstract: This paper deals with the study of a process that allows the use of waste sulphates from drywalls and plasterboards in the cement chemistry without affecting the resistance of cement, since cement industry is an important sulphate consumer. The role of the recycling temperature to obtain recycled calcium sulphates (RCS) and their SO3 contents, when RCS are used as set retarders in cements, is also studied. Gypsum from drywalls, and plaster of Paris from plasterboards, were heated at three recycling temperatures (110 °C −150 °C −170 °C) and partially dehydrated to obtain RCS. Chemical composition and SO3 purity of these RCS and of natural gypsums were determined and compared via XRD and DSC/TG. Setting time, the compressive strengths and the microstructure of cements with RCS used as set retarder were studied. The main products formed after cement hydration were determined by XRD and their microstructure observed by SEM/EDX. Internal porosity of different blends, area per mm 2 and diameter distribution, was determined through image processing with computer-aided design (CAD) software in SEM images. Cements with RCS from plasterboards as set retarder, with the higher SO3 content and higher amount of hemihydrates, preheated at 150–170 °C, have mechanical strengths according to cement standards. They show a denser microstructure, lower porosity and more homogeneous matrix after final setting than cements with RCS from drywalls. The selection here suggested of waste sulphates and the preheating process will allow using recycled sulphates from debris in the cement industry, according to EU standards.